Hyperglycemia-induced hemichorea-hemiballismus syndrome : a systematic review - Hoffmeister, Mariana Costa (2024)
Nonketotic hyperglycemia may occur as a cause of chorea in patients with chronic decompensated diabetes. Because it is rare and consequently poorly studied, diagnosis and treatment can be delayed. Therefore, our objective was to summarize clinical and radiological features, as well as treatments performed, from previously reported cases to facilitate adequate management in clinical practice. We searched MEDLINE/PubMed, EMBASE, Cochrane, CINAHL, Web of Science, Scopus, and LILACS databases for studies published before April 23, 2021. We included case reports and case series of adults (aged ≥18 years) that described hyperglycemic chorea with measurement of glycated hemoglobin (HbA1c) and cranial magnetic resonance imaging (MRI). Studies were excluded if participants were pregnant women, aged < 18 years, and had no description of chorea and/or physical examination. We found 121 studies that met the inclusion criteria, for a total of 214 cases. The majority of the included studies were published in Asia (67.3%). Most patients were women (65.3%) aged >65 years (67.3%). Almost all patients had decompensated diabetes upon arrival at the emergency department (97.2%). The most common MRI finding was abnormalities of the basal ganglia (89.2%). There was no difference in patient recovery between treatment with insulin alone and in combination with other medications. Although rare, hyperglycemic chorea is a reversible cause of this syndrome; therefore, hyperglycemia should always be considered in these cases.